Understanding and managing the interactive impacts of growth in urban land use and climate change on freshwater biota: A case study using the platypus (Ornithorhynchus anatinus). (16th December 2021) - Coleman, Rhys A.; Chee, Yung En; Bond, Nick R.; Weeks, Andrew; Griffiths, Josh; Serena, Melody; Williams, Geoff A.; Walsh, Christopher J.
Abstract: Globally, urban expansion and climate change interact to threaten stream ecosystems and are accelerating the loss of aquatic biodiversity. Waterway managers urgently need tools to understand the potential combined impacts of urbanization and climate change and to identify effective mitigating management interventions for protecting freshwater biota. We address this challenge using the semi‐aquatic mammal the platypus ( Ornithorhynchus anatinus ) as a focal species. We developed high‐resolution environmental spatial data for stream networks and spatially explicit habitat suitability models (HSMs) to explore the impact of threats and to identify the combination of management actions most likely to maintain or improve habitat suitability over the next 50 years in greater Melbourne, Australia. We developed and evaluated platypus HSMs (males‐and‐females and females‐only) including validation using an independent environmental DNA data set. Platypus occurred more commonly in larger, cooler streams with greater catchment‐weighted discharge, following periods of greater stream flow. They were positively associated with near‐stream forest cover and negatively associated with annual air temperature and urban stormwater runoff. Extensive reductions in suitable platypus habitat are predicted to occur under urbanization and climate change scenarios, with the greatest threat expected from reduced streamflows. This emphasizes the importance of maintaining flow regimes as part of conserving platypus in the region; however, substantial additional benefit is predicted by concurrent riparian revegetation and urban stormwater management efforts (that also have the potential to contribute to the streamflow objectives). Provision of adequate streamflows in a future with increasing water demands and water security requirements will likely require creative integrated water management solutions. Our high‐resolution stream network and HSMs have allowed predictions of potential range‐shifts due to urban expansion and climate change impacts at management‐relevant scales and at the whole‐of‐landscape scale. This has enabled systematic strategic planning, priority action planning and target setting in strategic policy development. Abstract : Using habitat suitability models, we explored the potential impact of urban growth and climate change on the distribution of threatened platypus ( Ornithorhynchus anatinus ) in Greater Melbourne, Victoria, Australia. We then identified the combination of management actions most likely to maintain or improve habitat suitability. Compared with the current distribution (1), we predict extensive reductions in suitable platypus habitat from our business‐as‐usual future scenario (2). The protection of natural flow regimes was identified as the most important action to protect platypus habitat, although, substantial additional benefit is predicted by concurrent riparian revegetation and urban stormwater management.